Evaluating Minimum Service Standards in Maritime Education and Training Delivery Units: A Secondary Data Analysis - Claudy Ananda Ginola; Abdul Sahid; Ambo Masse (Journal of Indonesian Scholars for Social Research, 2026)
Minimum Service Standards (Standar Pelayanan Minimal, SPM) provide an administrative and operational benchmark for ensuring that public service organizations deliver services with defined levels of quality, timeliness, accessibility, accountability, and user orientation. In maritime education and training, these standards have additional significance because service quality is directly connected to seafarer competence and maritime safety. This study evaluates the SPM framework applied to maritime education and training delivery units in Indonesia using secondary data and documentary analysis. The analysis draws on national public service legislation, Ministry of Transportation regulations, institutional service-standard documents, and the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW). The documents were coded into six evaluation dimensions: service accessibility, learning-process reliability, instructor competence, facilities and training infrastructure, assessment and certification, and accountability and user satisfaction. The findings indicate that the Indonesian regulatory framework provides a relatively comprehensive normative foundation, particularly through service standards covering admission, instructional processes, facilities, competency assessment, service time, costs, and complaint handling. However, the framework is stronger in specifying procedural and input requirements than in demonstrating outcome-based performance. The study therefore identifies the need for measurable service targets, periodic disclosure of performance results, stronger user-feedback mechanisms, and closer integration between public-service standards and STCW-based competency assurance. SPM effectiveness should be assessed not only by formal compliance but also by whether service standards consistently produce competent graduates, timely certification, transparent costs, and reliable user experiences.